IN VITRO EVALUATION OF FREE RADICAL SCAVENGING, FE2+ AND SNP-INDUCED LIPID PEROXIDATION (RAT BRAIN) ACTIVITIES OF METHANOLIC EXTRACTS FROM THREE (3) NORTHERN NIGERIAN PLANTS LEAF - Akinsanmi, Augustina Oduje; Johnson, Omolara Titilayo; Longdet, Ishaya Yohanna; Aguiyi, John Chinyere (Journal of Tropical Life Science, 2019)
Over the years research findings have shown that free radicals are the basis for many diseases. This study sought to investigate the free radical scavenging and inhibition of lipid peroxidation activities of some three Northern Nigerian plant leaf; Boswellia dalzielii Hutch. (Burseraceae) (BDL), Detarium microcarpum Guill. and Perr. (DML), and Daniellia oliveiri (Rolfe) Hutch. & Dalz (DOL). The study investigated both qualitative and quantitative phytochemical screening, free radical scavenging activities of 1, 1-diphenyl?2-picrylhydrazyl DPPH, total antioxidant capacity ABTS, hydroxyl, reducing property and inhibition of lipid peroxidation. All the seven phytochemicals screened were all present in both BDL and DML plant extracts but saponins and glycosides were absent in DOL plant leaf. The result revealed that BDL methanolic extract had the highest total flavonoid and phenolic content while BDL methanolic extract had the highest alkaloid content. DOL methanolic extract had the least content in all the 3 phytochemicals quantified. BDL methanolic extract had the highest free radical scavenging activity in 1, 1-diphenyl?2-picrylhydrazyl (DPPH), Hydroxyl and reducing power assays. While DML methanolic extract, had the highest free radical scavenging ability in 2, 2-azino-bis(3-ethylbenzazoline-6-sulphonic acid (TEAC) assays. The IC50 of BDL extract (12.37 mg/mL) was not significantly different (p > 0.05) from DML extract (10.39 mg/mL) in the Fe2+-induced lipid peroxidation assay. While, the IC50 of DML extract (14.83 mg/mL) was significantly higher (p < 0.05) than the BDL extract (19.92 mg/mL) in the SNP-induced lipid peroxidation. The DOL extract had the least scavenging and peroxidative inhibitory activity in all the assays carried out. We therefore concluded that the synergistic free radical scavenging activities and inhibition of lipid peroxidation of the three plants studied (especially, BDL and DML), provides a biochemical rationale for their usage as a medicinal plant.